A type of all-tab cylindrical lithium-ion battery
Patent Information
- Application Number
- CN202611198200.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种全极耳圆柱锂离子电池,以解决或改善上述技术问题
本发明通过定义正极极片的全极耳边与正极集流盘焊接连接处的接触内阻为R1,并控制0.1mΩ<R1≤0.5mΩ;将卷绕式电极组件的中心空腔直径dcore控制为外壳内径D1的8%~20%;将放电态下,卷绕式电极组件外径D2与外壳内径D1之间预留单边径向间隙ΔR,与电池满充时电极组件的径向膨胀量ΔR3结合起来,使ΔR/ΔR3为1.0~1.4。
Smart Images

Figure CN122992294A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a cylindrical lithium-ion battery with all tabs. Background Technology
[0002] In the pursuit of higher energy density and faster charging speeds in cylindrical lithium-ion batteries, existing technologies suffer from the following problems: On the positive electrode side, while high-nickel materials can improve energy density, their poor thermal stability makes them prone to oxygen release and violent exothermic reactions when heated or subjected to internal short circuits, resulting in a severe lack of safety margin. On the negative electrode side, silicon-based materials have become a key area for improvement due to their ultra-high theoretical capacity; however, the huge volume expansion during lithium intercalation causes particle pulverization, active material shedding, and repeated SEI film rupture, which not only drastically reduces cycle life but also generates significant radial stress within the cylindrical casing. Existing material-level buffering solutions are often disconnected from the cell structure design. Regarding current collection and heat generation, the traditional single-tab structure causes a sharp increase in ohmic internal resistance and localized heat generation as the cell size increases due to long-distance current collection, severely restricting fast charging performance and deteriorating temperature uniformity. In addition, in terms of safety protection, the existing PTC protection mechanism can cope with external short circuits or overcharging, but it is almost ineffective against internal short circuits and thermal runaway caused by extrusion, puncture, lithium plating, etc., and increasing the thickness of the high-resistivity coating will sacrifice room temperature rate and energy density.
[0003] In view of this, the present invention is proposed. Summary of the Invention
[0004] The purpose of this invention is to provide a fully tabbed cylindrical lithium-ion battery to solve or improve the above-mentioned technical problems.
[0005] This invention can be implemented as follows: This invention provides a cylindrical lithium-ion battery with multiple tabs, including a housing and a wound electrode assembly housed within the housing; the wound electrode assembly is formed by winding a positive electrode, a negative electrode, and a separator, and the wound electrode assembly simultaneously satisfies: (a) The contact resistance at the welding connection between the full-pole tab of the positive electrode and the positive current collector is R1, 0.1mΩ<R1≤0.5mΩ; (b) The wound electrode assembly has a central cavity extending through the housing along the axial direction, the diameter of which, dcore, is 8% to 20% of the inner diameter D1 of the housing; (c) In the discharge state, a single-sided radial gap ΔR is reserved between the outer diameter D2 of the wound electrode assembly and the inner diameter D1 of the outer shell, ΔR=(D1-D2) / 2, and ΔR and the radial expansion amount ΔR3 of the electrode assembly when the battery is fully charged satisfy: 1.0≤ΔR / ΔR3≤1.4.
[0006] In an optional implementation, 0.1mΩ < R1 ≤ 0.3mΩ.
[0007] In an optional embodiment, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The positive active material layer includes a composite system of layered lithium nickel cobalt manganese oxide particles and olivine-type lithium manganese iron phosphate particles. The mass percentage of olivine-type lithium manganese iron phosphate particles in the positive active material layer is x1, where 10% ≤ x1 ≤ 30%.
[0008] In an optional embodiment, the volume median particle size D of the olivine-type lithium manganese iron phosphate particles 50(LMFP) The volume median particle size D of layered lithium nickel cobalt manganese oxide particles is smaller than that of the layered lithium nickel cobalt manganese oxide particles. 50(NCM) And D 50(NCM) / D 50(LMFP) ≥3.
[0009] In an optional implementation, the constant current charge-discharge differential capacity curve (dQ / dV) of the positive electrode active material layer has at least one characteristic capacity peak in the ranges of 3.4V~3.6V and 3.9V~4.2V.
[0010] In an optional embodiment, at least one base coating layer is provided between the positive current collector and the positive active material layer; The primer layer comprises a polymer matrix, a conductive agent, and a ceramic filler; the sheet resistivity R0 of the primer layer at 25℃ meets the requirement of 0.05 Ω·cm. 2 ≤R0≤2Ω·cm 2 When the temperature rises to 30°C above the trigger temperature Ttrip, the ratio of the sheet resistance Rt to R0 satisfies Rt / R0≥100, where 100°C≤Ttrip≤140°C.
[0011] In an optional implementation, the thickness tp of the base coating satisfies 1μm≤tp≤3μm.
[0012] In an optional embodiment, the negative electrode has an extension δ at each of the axial ends of the electrode assembly relative to the positive electrode, where 0.3 mm ≤ δ ≤ 2.0 mm.
[0013] In an optional embodiment, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector. The negative active material in the negative active material layer includes silicon-carbon composite particles and a graphite matrix. The silicon-carbon composite particles include nano-silicon particles and a carbon coating layer covering the surface of the nano-silicon particles. The volume median particle size D of nano-silicon particles 50(Si) Satisfying 50nm≤D 50(Si) ≤200nm; The mass fraction W of the carbon coating in silicon-carbon composite particles C Satisfying 8%≤W C ≤20%; Based on elemental silicon, the silicon content W of the negative electrode Si Satisfying 8%≤W Si ≤20%.
[0014] In an optional implementation, the reversible specific capacity of the negative electrode active material is ≥450mAh / g.
[0015] In an optional implementation, ΔR3 = Σi(ti × ε); where ti is the single-sided thickness of the i-th negative electrode active material layer along the radial direction of the electrode assembly; ε is the single-layer negative electrode active material layer, 5% ≤ ε ≤ 20%, and ΔR3 is related to the negative electrode silicon content W. Si There is a positive correlation between them.
[0016] In an optional embodiment, the electrolyte in the all-tab cylindrical lithium-ion battery contains a film-forming additive, which includes fluoroethylene carbonate, and the fluoroethylene carbonate accounts for 3wt% to 15wt% of the electrolyte mass.
[0017] In an optional embodiment, the separator in the all-tab cylindrical lithium-ion battery is a ceramic-coated composite separator, the pore-closing temperature of the ceramic-coated composite separator is 130°C~160°C, and the thermal shrinkage rate is ≤5% at 150°C.
[0018] In an optional embodiment, the all-tab cylindrical lithium-ion battery is an all-tab cylindrical lithium-ion battery of model 21650.
[0019] In an optional embodiment, the all-tab cylindrical lithium-ion battery also has at least one of the following features: Feature 1: When a fully charged cylindrical lithium-ion battery is punctured by a steel needle with a diameter of 3-5mm, the maximum surface temperature of the cell is ≤110℃. Feature 2: The full-tab cylindrical lithium-ion battery retains ≥83% of its capacity when charged from 10% SOC to 80% SOC at a constant current of 6C at 25℃, compared to 1C charging. Feature 3: The DC internal resistance (DCIR) of the all-tab cylindrical lithium-ion battery at 25℃ and 50% SOC is ≤5mΩ; Feature 4: The mass energy density of the all-tab cylindrical lithium-ion battery is ≥250Wh / kg; Feature 5: The lifespan of the all-tab cylindrical lithium-ion battery is ≥1000 cycles under 1C / 1C, 25℃ conditions up to 80% SOH.
[0020] The beneficial effects of this invention include: This invention defines the contact resistance R1 at the welding connection between the full-pole tab of the positive electrode and the positive current collector as 0.1mΩ < R1 ≤ 0.5mΩ; controls the central cavity diameter dcore of the wound electrode assembly to be 8%~20% of the inner diameter D1 of the outer shell; and combines the single-sided radial gap ΔR reserved between the outer diameter D2 of the wound electrode assembly and the inner diameter D1 of the outer shell in the discharge state with the radial expansion amount ΔR3 of the electrode assembly when the battery is fully charged, so that ΔR / ΔR3 is 1.0~1.4.
[0021] The aforementioned positive electrode sheet uses the continuous, uncoated metal foil edge as the tab edge, welded to the positive current collector. The welding contact internal resistance is limited to a detectable low range to reduce ohmic heat generation. By setting a central cavity in the core and reserving a radial gap between the core outer diameter and the shell inner diameter according to the expansion amount of the negative electrode silicon, with 1.0≤ΔR / ΔR3≤1.4, the higher the negative electrode silicon content, the larger the reserved gap. The low internal resistance heat generation of the tab, combined with the current-limiting response of the high-resistance bottom coating and the chemical buffering of the composite positive electrode, controls the internal short-circuit heat generation below the threshold. The all-tab cylindrical lithium-ion battery that meets the above characteristics can combine high energy density, fast charging capability, and high safety. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is an axial cross-sectional view of the all-tab cylindrical lithium-ion battery provided by the present invention.
[0024] Icons: 1-Outer shell; 2-Wound electrode assembly; 3-Central cavity; 4-Positive current collector; 5-Negative current collector; 6-Top cover; 7-Bottom of shell. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0026] The following is a detailed description of the all-tab cylindrical lithium-ion battery provided by the present invention.
[0027] The all-tab cylindrical lithium-ion battery provided by this invention, such as... Figure 1As shown, it includes a housing 1, a wound electrode assembly housed within the housing 1, and a positive current collector 4 and a negative current collector 5 that are electrically connected to both ends of the wound electrode assembly.
[0028] The wound electrode assembly is composed of a positive electrode sheet, a negative electrode sheet, and a separator wound together. The wound electrode assembly simultaneously satisfies the following requirements: (a) The contact resistance at the welding connection between the full-pole tab of the positive electrode and the positive current collector 4 is R1, 0.1mΩ<R1≤0.5mΩ.
[0029] The aforementioned positive electrode sheet has a continuous, uncoated metal foil edge extending along its length as a full-electrode tab. This full-electrode tab is gathered, flattened, and then welded to the positive current collector 4. For example, the full-electrode tab can be connected to the current collector via a two-step process: ultrasonic pre-welding and laser welding. The positive current collector 4 is electrically connected to the top cover 6, forming a low-resistance current path for end-face current collection.
[0030] In some optional implementations, R1 can be 0.15mΩ, 0.2mΩ, 0.25mΩ, 0.3mΩ, 0.35mΩ, 0.4mΩ, 0.45mΩ, or 0.5mΩ, or other values within the range of 0.1mΩ (excluding) to 0.5mΩ. In some preferred implementations, 0.1mΩ < R1 ≤ 0.3mΩ.
[0031] In some optional embodiments, the contact resistance at the welded connection between the full-pole tab of the negative electrode sheet and the negative current collector 5 is R2, where 0.1mΩ < R2 ≤ 0.5mΩ. The aforementioned negative electrode sheet has a continuous, uncoated metal foil edge extending along its length as a full-pole tab. This full-pole tab is gathered, flattened, and then welded to the negative current collector 5. Exemplarily, the full-pole tab can be connected to the current collector via a two-step process: ultrasonic pre-welding and laser welding. The negative current collector 5 is electrically connected to the bottom of the housing 7, forming a low-resistance current path for end-face current collection. In some optional embodiments, R2 can be 0.15mΩ, 0.2mΩ, 0.25mΩ, 0.3mΩ, 0.35mΩ, 0.4mΩ, 0.45mΩ, or 0.5mΩ, or other values within the range of 0.1mΩ (excluding) to 0.5mΩ. In some preferred embodiments, 0.1mΩ < R2 ≤ 0.3mΩ.
[0032] (b) The wound electrode assembly has a central cavity 3 that extends through the axial direction of the housing 1, and the diameter dcore of the central cavity 3 is 8% to 20% of the inner diameter D1 of the housing.
[0033] In some alternative implementations, the diameter dcore of the central cavity 3 can be 8%, 10%, 12%, 15%, 18% or 20% of the inner diameter D1 of the outer shell, or other values within the range of 8% to 20%.
[0034] (c) In the discharge state, a single-sided radial gap ΔR is reserved between the outer diameter D2 of the wound electrode assembly and the inner diameter D1 of the outer shell, ΔR=(D1-D2) / 2, and ΔR and the radial expansion amount ΔR3 of the electrode assembly when the battery is fully charged satisfy: 1.0≤ΔR / ΔR3≤1.4.
[0035] In some optional implementations, ΔR / ΔR3 can be 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, or 1.4, or other values within the range of 1.0 to 1.4. ΔR / ΔR3 characterizes the degree of matching between the "reserved gap" and the "full-charge expansion amount." The higher the silicon content of the negative electrode, the larger the reserved unilateral radial gap ΔR.
[0036] The positive and negative electrodes are respectively welded to the current collector using the edges of continuous, uncoated metal foil as the all-electrode tabs. The internal resistance of the welding contact is limited to a detectable low value range to reduce ohmic heat generation. By setting a central cavity 3 in the core and reserving a radial gap between the outer diameter of the core and the inner diameter of the shell according to the expansion amount of the negative electrode silicon, and 1.0≤ΔR / ΔR3≤1.4, the higher the silicon content of the negative electrode, the larger the reserved gap. The low internal resistance heat generation of the all-electrode tab, combined with the current-limiting response of the high-resistance bottom coating and the chemical buffer of the composite positive electrode, controls the internal short-term heat generation below the threshold.
[0037] In this invention, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side surface of the positive current collector. The positive active material layer includes a composite system of layered lithium nickel cobalt manganese oxide particles and olivine-type lithium manganese iron phosphate particles.
[0038] The mass percentage of the above-mentioned olivine-type lithium manganese iron phosphate particles in the positive electrode active material layer is x1, where 10% ≤ x1 ≤ 30%. For example, x1 can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, or 30%, or other values within the range of 10% to 30%.
[0039] The cathode of this invention is a composite of high-nickel NCM and olivine-type lithium manganese iron phosphate (LMFP) in the above mass ratio. Utilizing the excellent structure and thermal stability of the olivine phase, a dispersed "safety buffer phase" is formed between the high-nickel particles, which suppresses the chain exothermic reaction when heated or in the short term, and contributes capacity without sacrificing electrochemical performance.
[0040] In some optional embodiments, the molar percentage of nickel in the layered lithium nickel cobalt manganese oxide particles is ≥60%.
[0041] In some alternative embodiments, the molecular formula of the olivine-type lithium manganese iron phosphate particles is LiMn. y Fe (1-y)PO4, where 0.5≤y≤0.8.
[0042] In some alternative embodiments, the volume median particle size D of the olivine-type lithium manganese iron phosphate particles 50(LMFP) The volume median particle size D of layered lithium nickel cobalt manganese oxide particles is smaller than that of the layered lithium nickel cobalt manganese oxide particles. 50(NCM) And D 50(NCM) / D 50(LMFP) ≥3. Through the above arrangement, small-diameter olivine-type lithium manganese iron phosphate particles are filled between large-diameter layered lithium nickel cobalt manganese oxide particles, forming a continuous isolation and buffer network when heated.
[0043] In some alternative implementations, the constant current charge-discharge differential capacity curve (dQ / dV) of the positive electrode active material layer has at least one characteristic capacity peak in the ranges of 3.4V~3.6V and 3.9V~4.2V.
[0044] In some alternative embodiments, the positive electrode sheet can be prepared as follows: layered lithium nickel cobalt manganese oxide particles and olivine-type lithium manganese iron phosphate particles (LiMn) are mixed according to a mass percentage of x1 in the positive electrode active material layer. 0.6 Fe 0.4 PO4 premix; conductive carbon black and carbon nanotubes are added as conductive agents, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) is used as a solvent. The mixture is dispersed in stages at high speed in a vacuum double planetary mixer to obtain a positive electrode slurry. After filtration through a sieve, the slurry is coated on both sides of a pre-prepared base coating positive electrode current collector (aluminum foil) using a slot extrusion coating machine. After multi-stage drying, rolling to the designed compaction density, and slitting, the positive electrode sheet is obtained.
[0045] In some alternative embodiments, an undercoat layer is provided at least between the positive current collector and the positive active material layer. The undercoat layer comprises a polymer matrix, a conductive agent, and a ceramic filler.
[0046] The sheet resistivity R0 of the base coating at 25℃ satisfies 0.05Ω·cm. 2 ≤R0≤2Ω·cm 2 For example, R0 can be 0.05 Ω·cm 2 0.1Ω·cm 2 0.5Ω·cm 2 1Ω·cm 2 1.5Ω·cm 2 or 2Ω·cm 2 Etc., can also be 0.05Ω·cm 2 ~2Ω·cm 2 Other values within the range.
[0047] When the temperature rises to 30°C above the trigger temperature Ttrip, the ratio of the sheet resistance Rt to R0 satisfies Rt / R0 ≥ 100, where 100°C ≤ Ttrip ≤ 140°C. For example, Ttrip can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, or 140°C, or other values within the range of 100°C to 140°C.
[0048] In some optional embodiments, the thickness tp of the undercoat satisfies 1μm ≤ tp ≤ 3μm. For example, tp can be 1μm, 1.5μm, 2μm, 2.5μm or 3μm, or other values in the range of 1μm to 3μm.
[0049] By setting a positive temperature coefficient (PTC) high-resistivity bottom coating at least between the positive current collector and the positive active material layer, its surface resistance at room temperature is limited to a low range that does not impair the rate capability. Above the trigger temperature, the surface resistance jumps sharply, forming an internal short current-limiting interface between the current collector and the active layer, thereby limiting and interrupting the internal short current.
[0050] In some alternative embodiments, the above-mentioned base coating can be prepared as follows: a crystalline positive temperature coefficient polymer matrix (such as polyethylene), a conductive agent (such as conductive carbon black), and a ceramic filler (such as boehmite) are dispersed in xylene at a mass ratio of polymer matrix, conductive agent, and ceramic filler of 70:5:25, and ground to obtain a high-resistivity base coating slurry with uniform particle size; a continuous base coating layer of tp thickness is coated on the surface of the positive electrode aluminum foil by microgravure or slit method and cured at low temperature.
[0051] In this invention, the negative electrode sheet extends by an amount δ at both ends of the electrode assembly relative to the positive electrode sheet, with a value of 0.3mm ≤ δ ≤ 2.0mm. For example, δ can be 0.3mm, 0.5mm, 0.8mm, 1.0mm, 1.2mm, 1.5mm, 1.8mm, or 1.9mm, or other values within the range of 0.3mm to 2.0mm (excluding 2.0mm).
[0052] In this invention, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector. The negative active material in the negative active material layer includes silicon-carbon composite particles and a graphite matrix. The silicon-carbon composite particles include nano-silicon particles and a carbon coating layer covering the surface of the nano-silicon particles.
[0053] In some alternative embodiments, the silicon nanoparticles can be prepared by grinding. The silicon-carbon composite particles can consist of silicon nanoparticles prepared by grinding and an in-situ graphitized carbon layer conformally coated on their surface. The aforementioned carbon coating layer has the functions of conducting electricity, buffering expansion, and suppressing side reactions, which is beneficial for achieving a balance between high specific capacity and long cycling performance.
[0054] For example, using industrial silicon powder as raw material, the organic solvent N-methylpyrrolidone (NMP) and the dispersant polyvinylpyrrolidone (PVP) are added, and the silicon particles are refined to a preset D value by wet grinding in a sand mill. 50(Si) Nano-silicon slurry was obtained; the obtained nano-silicon slurry was mixed with liquid carbon precursor (asphalt) and spray-dried to conformally coat the nano-silicon surface with the precursor; then, under the protection of an inert atmosphere, it was pre-carbonized at 900℃ and then graphitized to transform the carbon precursor in situ into a conformal graphitized carbon shell with the functions of conducting electricity, buffering expansion and inhibiting side reactions, thus obtaining silicon-carbon composite particles with carbon coating.
[0055] In some alternative embodiments, the volume median particle size D of the silicon nanoparticles 50(Si) Satisfying 50nm≤D 50(Si) ≤200nm. For example, D 50(Si) It can be 50nm, 80nm, 100nm, 120nm, 150nm, 180nm or 200nm, or other values within the range of 50nm to 200nm.
[0056] In some alternative embodiments, the mass fraction W of the carbon coating layer in the silicon-carbon composite particles C Satisfying 8%≤W C ≤20%. For example, W C It can be 8%, 10%, 12%, 15%, 18% or 20%, or other values within the range of 8% to 20%.
[0057] In some alternative implementations, the silicon content W of the negative electrode is calculated based on elemental silicon. Si Satisfying 8%≤W Si ≤20%. For example, W Si It can be 8%, 10%, 12%, 15%, 18%, or 20%, or other values within the range of 8% to 20%. That is, W Si This can be understood as the mass percentage of Si in the negative electrode active material layer.
[0058] In some alternative implementations, the reversible specific capacity of the negative electrode active material is ≥450mAh / g.
[0059] In some alternative implementations, the above-mentioned ΔR3 and W Si Positive correlation, ΔR3=Σi(ti×ε); where ti is the single-sided thickness of the i-th negative electrode active material layer along the radial direction of the electrode assembly; ε is the full-fill expansion rate of a single negative electrode active material layer, ε varies with W SiIt increases monotonically, with 5% ≤ ε ≤ 20%. For example, ε can be 5%, 8%, 10%, 12%, 15%, 18%, or 20%, or other values within the range of 5% to 20%.
[0060] In some alternative embodiments, the negative electrode sheet can be prepared as follows: silicon-carbon composite particles are combined with artificial graphite according to a preset negative electrode silicon content; a water-based negative electrode slurry is obtained by dispersing sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) as an aqueous binder, conductive carbon black as a conductive agent, and deionized water as a solvent in a double planetary mixer; the negative electrode slurry is coated on both sides of the negative electrode current collector (copper foil), dried, rolled, and slit into sheets, and the negative electrode is reserved with an extension amount δ at both ends of the electrode assembly relative to the positive electrode.
[0061] In some optional embodiments, the electrolyte in the all-tab cylindrical lithium-ion battery includes a film-forming additive. The film-forming additive includes fluoroethylene carbonate (FEC), and the FEC constitutes 3 wt% to 15 wt% of the electrolyte mass, used to construct an elastic SEI on the silicon-carbon anode surface to accommodate silicon expansion. Exemplarily, the FEC constitutes 3 wt%, 5 wt%, 8 wt%, 10 wt%, 12 wt%, or 15 wt% of the electrolyte mass, or other values within the range of 3 wt% to 15 wt%.
[0062] In some optional embodiments, the separator in the all-tab cylindrical lithium-ion battery is a ceramic-coated composite separator with a pore-closing temperature of 130°C to 160°C (such as 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, or 160°C), and a thermal shrinkage rate of ≤5% at 150°C, so as to form a multi-level thermal runaway protection together with the composite positive electrode and the high-resistivity bottom coating.
[0063] In some alternative embodiments, the all-tab cylindrical lithium-ion battery is a 21650 all-tab cylindrical lithium-ion battery. Alternatively, the casing 1 can be understood as a 21650 specification cylindrical casing.
[0064] In some alternative implementations, when a fully charged cylindrical lithium-ion battery is punctured by a steel needle with a diameter of 3-5 mm, the maximum surface temperature of the cell is ≤110°C, and it does not catch fire or explode.
[0065] In some alternative implementations, the all-tab cylindrical lithium-ion battery is charged from 10% SOC to 80% SOC at a constant current of 6C at 25°C, with a capacity retention of ≥83% relative to 1C charging.
[0066] In some alternative implementations, the DC internal resistance (DCIR) of the all-tab cylindrical lithium-ion battery at 25°C and 50% SOC is ≤5mΩ (21650 specification).
[0067] In some alternative implementations, the mass energy density of the all-tab cylindrical lithium-ion battery is ≥250Wh / kg.
[0068] In some alternative implementations, the all-tab cylindrical lithium-ion battery has a lifespan of ≥1000 cycles at 1C / 1C, 25°C to 80% SOH.
[0069] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0070] Example 1 This embodiment provides a 21650 specification all-tab cylindrical lithium-ion battery, the preparation of which includes: S1: Prepare a positive current collector with a base coating.
[0071] A crystalline positive temperature coefficient polymer matrix (polyethylene), a conductive agent (conductive carbon black), and a ceramic filler (boehmite) were dispersed in xylene at a mass ratio of 70:5:25. The mixture was then ground to obtain a high-resistivity undercoating slurry with uniform particle size. A continuous undercoating layer with a thickness of tp = 2 μm was then coated onto the surface of the positive electrode aluminum foil using a micro-gravure or slit method and cured at low temperature, resulting in a sheet resistivity R0 of approximately 0.5 Ω·cm at 25°C. 2 The trigger temperature (Ttrip) is approximately 120℃, and at (Ttrip + 30℃) Rt / R0 ≈ 5 × 10².
[0072] S2: Preparation of positive electrode slurry and positive electrode sheet.
[0073] Assuming the mass percentage of olivine-type lithium manganese iron phosphate particles in the positive electrode active material layer is x1 = 15%, layered lithium nickel cobalt manganese oxide particles (with a nickel molar percentage of approximately 83%, D) are added. 50(NCM) Approximately 12 μm) and olivine-type lithium manganese iron phosphate particles LiMn 0.6 Fe 0.4 PO4 (D) 50(LMFP) Approximately 1.5 μm, D 50(NCM) / D 50(LMFP) ) 8) Premix the active material at a mass ratio of 85:15; add conductive carbon black and carbon nanotubes as conductive agents, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a solvent. Disperse the mixture in stages at high speed in a vacuum double planetary mixer at a mass ratio of active material:conductive agent:binder = 96:2:2 to obtain a uniform positive electrode slurry with a solid content of approximately 70wt%. After filtration through a sieve, the slurry is coated on both sides of a pre-prepared base coating positive electrode current collector (aluminum foil) using a slot extrusion coating machine. After multi-stage drying at 110℃~120℃, rolling to the designed compaction density, and slitting, the positive electrode sheet is obtained.
[0074] S3: Prepare silicon-carbon composite particles.
[0075] Using industrial silicon powder as raw material, an organic solvent (N-methylpyrrolidone (NMP)) and a dispersant (polyvinylpyrrolidone (PVP)) are added, and the silicon particles are refined to a median particle size D by wet grinding in a sand mill. 50(Si) The silicon nanoparticles were obtained with a particle size of approximately 100 nm. The resulting silicon nanoparticles were mixed with a liquid carbon precursor (asphalt) at a mass ratio of approximately 1:0.3 and spray-dried to conformally coat the surface of the silicon nanoparticles. Subsequently, the mixture was pre-carbonized at 900 °C under an inert atmosphere and then graphitized to transform the carbon precursor into a conformal graphitized carbon shell (i.e., a carbon coating layer) in situ, resulting in silicon-carbon composite particles with a carbon coating layer mass fraction (WC) of approximately 12%.
[0076] S4: Prepare negative electrode slurry and negative electrode sheet.
[0077] The above-mentioned silicon-carbon composite particles are combined with artificial graphite to obtain the negative electrode active material, such that the negative electrode silicon content W, calculated based on elemental silicon, is... Si The anode content was 12% (the reversible specific capacity of the negative electrode was approximately 520 mAh / g). A water-based negative electrode slurry with a solid content of 45 wt% was obtained by dispersing sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) as an aqueous binder, conductive carbon black as a conductive agent, and deionized water as a solvent in a double planetary mixer. The mass ratio of the negative electrode active material, CMC, SBR, and conductive agent was 95:1.5:2.5:1. The negative electrode slurry was coated on both sides of a copper foil current collector, dried, rolled, and slit into sheets, with the negative electrode extending δ by 1.0 mm from each end of the electrode assembly relative to the positive electrode.
[0078] S5: Prepare the all-pole ear wound electrode assembly 2.
[0079] During coating, continuous uncoated metal foil edges (aluminum foil and copper foil, respectively) are reserved along the length of the positive and negative electrode sheets to serve as full electrode tabs. The positive electrode sheet, ceramic-coated composite diaphragm (closed-cell temperature of about 140°C), and negative electrode sheet are stacked in sequence and wound into a cylindrical core on a winding machine. The winding tension and center needle diameter are controlled so that the core has a central cavity 3 with a diameter of about 2.0 mm (about 10% of the inner diameter D1 of the outer shell) that runs through the axis. After winding, the continuous foil edges of the positive and negative electrodes are concentrated at the upper and lower ends of the core to form full electrode tabs.
[0080] S6: Current collector welding and cell assembly.
[0081] The extended edges of the full-pole tabs at the upper and lower ends of the core are gathered and flattened to form dense end faces, which are then welded to the positive current collector 4 and the negative current collector 5 through a two-step process of ultrasonic pre-welding and laser welding, so that the welding contact internal resistance R1=0.2mΩ and R2=0.2mΩ. The positive current collector 4 is electrically connected to the top cover 6, and the negative current collector 5 is electrically connected to the 21650 steel shell bottom 7, forming a low internal resistance current path for end face current collection. The core is then installed into the steel shell, and a single-sided radial gap ΔR is reserved in the discharge state so that the expansion adaptation coefficient ΔR / ΔR3=1.2.
[0082] S7: Electrolyte preparation, injection and formation.
[0083] A basic electrolyte containing 1.0 mol / L LiPF6 was prepared using a mixed solvent of EC, EMC, and DMC in a volume ratio of 3:5:2, and fluoroethylene carbonate (FEC) film-forming additives were added at 8 wt% of the electrolyte mass. The electrolyte was injected into the battery cell via vacuum injection, sealed, and allowed to stand for wetting. Subsequently, formation (first small current charge and discharge) was performed to construct a LiF-rich elastic SEI film on the surface of the silicon-carbon anode. After capacity testing and aging, the finished 21650 all-tab cylindrical lithium-ion battery was obtained.
[0084] Example 2 The only difference between this embodiment and Embodiment 1 is that x1 = 10%.
[0085] Example 3 The only difference between this embodiment and Embodiment 1 is that x1 = 20%.
[0086] Example 4 The only difference between this embodiment and Embodiment 1 is that x1 = 30%.
[0087] Comparative Example 1 The only difference between this comparative example and Example 1 is that x1 = 5%.
[0088] Comparative Example 2 The only difference between this comparative example and Example 1 is that x1 = 40%.
[0089] Example 5 The only difference between this embodiment and Embodiment 1 is that: W Si =8%, and simultaneously reduce the reserved gap ΔR to maintain the expansion adaptation coefficient ΔR / ΔR3=1.2.
[0090] Example 6 The only difference between this embodiment and Embodiment 1 is that: W Si =15%, and simultaneously increase the reserved gap ΔR to maintain the expansion adaptation coefficient ΔR / ΔR3=1.2.
[0091] Example 7 The only difference between this embodiment and Embodiment 1 is that: W Si =20%, and simultaneously increase the reserved gap ΔR to maintain the expansion adaptation coefficient ΔR / ΔR3=1.2.
[0092] Comparative Example 3 The only difference between this comparative example and Example 1 is that: W Si =5%, and simultaneously adjust ΔR to maintain ΔR / ΔR3=1.2.
[0093] Comparative Example 4 The only difference between this comparative example and Example 1 is that: W Si =25%, and simultaneously adjust ΔR to maintain ΔR / ΔR3=1.2.
[0094] Example 8 The only difference between this embodiment and Embodiment 1 is that the thickness of the base coating is tp = 1.0 μm.
[0095] Example 9 The only difference between this embodiment and Embodiment 1 is that the thickness of the base coating is tp = 1.5 μm.
[0096] Example 10 The only difference between this embodiment and Embodiment 1 is that tp = 3.0 μm.
[0097] Comparative Example 5 The only difference between this comparative example and Example 1 is that tp = 0.3 μm.
[0098] Comparative Example 6 The only difference between this comparative example and Example 1 is that tp = 5.0 μm.
[0099] Example 11 The only difference between this embodiment and Embodiment 1 is that the reserved gap is reduced so that ΔR / ΔR3=1.0.
[0100] Example 12 The only difference between this embodiment and Embodiment 1 is that the reserved gap is increased so that ΔR / ΔR3=1.3.
[0101] Example 13 The only difference between this embodiment and Embodiment 1 is that the reserved gap is increased so that ΔR / ΔR3=1.4.
[0102] Comparative Example 7 The only difference between this comparative example and Example 1 is that the reserved gap is reduced so that ΔR / ΔR3=0.8.
[0103] Comparative Example 8 The only difference between this comparative example and Example 1 is that the reserved gap is increased so that ΔR / ΔR3=1.8.
[0104] Example 14 The only difference between this embodiment and Embodiment 1 is that R1 = 0.3mΩ.
[0105] Example 15 The only difference between this embodiment and Embodiment 1 is that R1 = 0.4mΩ.
[0106] Example 16 The only difference between this embodiment and Embodiment 1 is that R1 = 0.5mΩ.
[0107] Comparative Example 9 The only difference between this comparative example and Example 1 is that R1 = 0.1 mΩ.
[0108] Comparative Example 10 The only difference between this comparative example and Example 1 is that R1 = 0.8 mΩ.
[0109] Test case The performance of the 21650 all-tab cylindrical lithium-ion batteries obtained in Examples 1-16 and Comparative Examples 1-10 was compared, and the test methods are as follows.
[0110] 1. Cross-sectional scanning electron microscopy (SEM). Finished or semi-finished electrode sheets are prepared with a flat cross-section through ion milling or cryo-slicing, and observed under a scanning electron microscope. This is used to measure and determine the thickness tp of the high-resistivity undercoat, the thickness of the positive / negative electrode active material layers, and the conformal coating morphology of the in-situ graphitized carbon shell on the surface of the nano-silicon particles. Combined with backscattering and energy dispersive spectroscopy (EDS), the interfacial layers of the current collector, undercoat, and active layer can be distinguished.
[0111] 2. Thermogravimetric analysis (TGA). A sample of silicon-carbon composite particles was taken and heated at a constant rate in air. The carbon component oxidized and lost weight, while the silicon component was largely retained. The mass fraction W of the carbon coating layer in the silicon-carbon composite particles was quantitatively calculated based on the weight loss step. C .
[0112] 3. Laser particle size analysis. NCM, LMFP, or nano-silicon powders are dispersed in a dispersion medium and ultrasonically dispersed. The volumetric particle size distribution is determined using a laser diffractometer to obtain the Dsize. 50(Si) D 50(NCM) and D 50(LMFP) .
[0113] 4. Four-probe method for surface resistivity and temperature response testing. The current collector sample with a high-resistivity undercoat is placed on a temperature-controlled heating stage. The surface resistivity of the undercoat block is measured using a four-probe tester at 25℃ and (Ttrip+30℃) to obtain the surface resistivity R0 at room temperature and Rt at high temperature, and the jump ratio Rt / R0 is calculated. By continuously heating and recording the surface resistivity-temperature curve, the trigger temperature Ttrip can be determined.
[0114] 5. Four-terminal micro-ohmmeter contact internal resistance test. Disassemble the battery cell in the discharged state, remove the current collector-to-all tab welded body, and use a four-terminal (Kelvin) micro-ohmmeter to measure the contact internal resistance Rtab at the welded interface between the all tab and the current collector under constant current.
[0115] 6. Constant Current Charge-Discharge Differential Capacity Curve (dQ / dV). The cell or cathode half-cell is subjected to constant current charge-discharge at a low rate. Capacity-voltage data are recorded, and the voltage is differentiated to obtain the dQ / dV-voltage curve. Characteristic capacity peaks appearing in the 3.4V~3.6V and 3.9V~4.2V ranges are identified. These peaks correspond to the electrochemical responses of olivine-phase LMFP and high-nickel NCM, respectively, thus determining the two-phase composition of the composite cathode.
[0116] 7. Structural Dimension Measurement (Micrometer Caliper and Cross-Section Optical Microscope). Disassemble the battery cell in the discharged state and measure the inner diameter D1 of the outer shell, the outer diameter D2 of the core, the diameter dcore of the central cavity 3, and the amount of negative electrode protruding relative to positive electrode δ using a digital micrometer caliper and a cross-section optical microscope. Calculate the single-sided radial clearance in the discharged state using ΔR=(D1-D2) / 2. The full-charge expansion amount ΔR3 is obtained from the difference between the disassembled dimensions in the fully charged and discharged states, or it can be estimated using ΔR3=Σ(ti×ε).
[0117] 8. Mass energy density test. Discharge the cell to the cutoff voltage at a low rate (e.g., 0.33C) at a specified temperature, record the discharge energy (Wh), and divide it by the measured mass of the cell (kg) to obtain the mass energy density (Wh / kg).
[0118] 9.6C Fast Charging Capacity Retention Rate Test. At 25℃, the baseline capacity was first measured by charging at 1C, and then the battery was charged from 10% SOC to 80% SOC at a constant current of 6C. The ratio of the capacity charged in this range to the capacity of the corresponding range of 1C charging was used as the 6C fast charging capacity retention rate.
[0119] 10. DC Internal Resistance (DCIR) Test. Apply a constant current discharge pulse (e.g., 10s pulse) of a specified amplitude to the cell at 25℃ and 50% SOC. Calculate the DC internal resistance (DCIR) by the ratio of the voltage difference before and after the pulse to the current amplitude.
[0120] 11. Cycle life test. The cell is continuously charged and discharged at 1C at 25℃. The discharge capacity decays with the number of cycles. The cycle life is evaluated by the number of cycles when the capacity decays to 80% of the initial capacity (i.e., 80% SOH).
[0121] 12. Needle penetration safety test. Charge the battery cell to full charge. Referring to the relevant method in GB38031, use a 4mm diameter steel needle to vertically puncture the battery cell at a specified speed. Record the highest surface temperature of the battery cell during the puncture process and whether it catches fire or explodes.
[0122] The test results are shown in Tables 1 to 5.
[0123] Table 1. Effect of olivine phase mass fraction x1
[0124] As shown in Table 1, when the size of olivine-type lithium manganese iron phosphate (LMFP) particles increases within a certain range, the maximum needle penetration temperature decreases monotonically, the cycle life increases slightly, and the mass energy density gradually decreases. This is because olivine-type LMFP has a stable polyanionic framework, and its delithiated state does not easily release oxygen. Dispersed among high-nickel NCM particles, it can act as an "inert isolation and endothermic buffer phase" during heating or short periods, blocking the chain-like exothermic reaction between the high-nickel cathode and the electrolyte, thus significantly suppressing temperature rise.
[0125] In Comparative Example 1, x1 was less than 5%, resulting in a discontinuous buffer phase and a needle penetration temperature as high as 140°C, leading to fire failure. In Comparative Example 2, x1 was more than 40%, with an excessively high proportion of low-voltage, low-capacity olivine phase, causing the mass energy density to drop to 224Wh / kg, which no longer met the high specific energy target.
[0126] In addition, x1 has a relatively small impact on DCIR. As x1 increases from 5% to 40%, DCIR only increases slowly from 3.5mΩ to 4.8mΩ. Therefore, controlling x1 between 10% and 30% can balance a better safety margin and energy density.
[0127] Table 2. Silicon content (W) of the negative electrode Si Impact
[0128] Table 2 shows that increasing silicon content improves energy density, but decreases cycle life and exacerbates full-charge expansion. This is because silicon's high lithium intercalation capacity is beneficial for increasing energy density, while its lithium intercalation volume expansion intensifies with increasing content, leading to increased stress on the carbon shell and electrode structure, repeated SEI cracking, loss of contact between active materials, and accelerated cycle degradation. When W SiWithin the range of 8% to 20%, the in-situ graphitized carbon shell and the expansion-adaptive winding structure can accommodate expansion, which is cyclically controllable, and the DCIR only slightly increases from 3.8mΩ to 4.1mΩ.
[0129] Comparative Example 3 W Si Below 5%, the corresponding energy density is only 236 Wh / kg; compared to Comparative Example 4, W Si Above 25%, the corresponding expansion is as high as 10.5%, the cycle life drops sharply to 620 cycles, and the DCIR rises to 4.9 mΩ due to contact degradation caused by severe expansion-contraction. 12% achieves the optimal balance between energy density and cycle life.
[0130] Table 3. Effect of high-resistivity undercoating thickness tp
[0131] As shown in Table 3, the needle penetration temperature continues to decrease as the base coating thickness increases, but the DCIR increases, and the fast charging and energy density decrease slightly. This is because the positive temperature coefficient high-resistivity base coating maintains low surface resistivity at room temperature, without compromising rate capability; once the local temperature rise in the internal short circuit exceeds the trigger temperature, the surface resistivity of the base coating increases sharply (Rt / R0≥100), limiting the short-circuit current in situ and cutting off the Joule heat source. When tp is 1μm~3μm, it can achieve both superior protection and rate capability.
[0132] The base coating of Comparative Example 5 was too thin, resulting in discontinuity of the high-resistivity phase and failure to flow through, and it failed to pass the needle penetration temperature of 136℃; the base coating of Comparative Example 6 was too thick, resulting in excessively high internal resistance and inactive content at room temperature, causing the 6C retention rate to drop to 80% and the DCIR to rise to 6.3mΩ.
[0133] Table 4. Effect of expansion fit coefficient ΔR / ΔR3
[0134] As can be seen from Table 4, within the range of ΔR / ΔR3 of 1.0 to 1.4, as ΔR / ΔR3 increases, the expansion deformation decreases, the cycle improves, but the energy density decreases.
[0135] In Comparative Example 7, the ΔR / ΔR3 ratio was too low, meaning the gap was insufficient to accommodate silicon expansion. This caused mechanical stress and localized lithium plating due to the core pressing against the casing, resulting in a sharp drop in cycle life to 480 cycles, 11% casing bulging, and internal shorting induced by internal pressure deformation, leading to needle-punch failure. Simultaneously, the core compression worsened interlayer contact and increased the risk of internal shorting, resulting in a DCIR as high as 7.2 mΩ. In Comparative Example 8, the ΔR / ΔR3 ratio was too high, leading to wasted gaps, reduced active material per unit casing, a decrease in mass energy density to 236 Wh / kg, and increased contact resistance due to winding relaxation, with the DCIR rising to 5.6 mΩ.
[0136] Table 5. Influence of contact internal resistance R1 during all-pole tab welding
[0137] As shown in Table 5, R1 directly affects DCIR. When R1 increases within a certain range, DCIR increases monotonically, and the 6C fast charging retention rate decreases. This is because higher contact resistance directly increases ohmic polarization and heat generation during fast charging. However, lower contact resistance is not always better. In Comparative Example 9, R1 is too low, usually requiring excessive soldering, which easily causes foil erosion, burrs, and microcracks, weakening mechanical strength and inducing internal short circuits after vibration or abuse, resulting in premature cycle decay to 900 cycles and safety failure. In Comparative Example 10, R1 is too high, with DCIR reaching 6.3mΩ and the 6C retention rate only 78%. When R1 is in the range of 0.1mΩ (excluding) to 0.5mΩ, both low heat generation and soldering reliability can be balanced.
[0138] In summary, by controlling ΔR / ΔR3 to 1.0~1.4 and R1 to 0.1mΩ (excluding)~0.5mΩ, this invention effectively correlates the structural gap with the silicon content of the negative electrode, resulting in a lower internal resistance for the 21650 all-tab cylindrical lithium-ion battery. Furthermore, by limiting the room-temperature surface resistivity of the high-resistivity undercoating to 0.05Ω·cm... 2 ~2Ω·cm 2 Simultaneously, the resistance jump ratio Rt / R0 after triggering is controlled to be ≥100, and it is coordinated with the chemical buffer of the composite positive electrode and the low heat generation of the all-tab to form in-situ current limiting for internal short circuits. Furthermore, the composite positive electrode, high-silicon negative electrode, high-resistivity undercoating, and all-tab structure are integrated into the same cylindrical cell. High nickel and high silicon can jointly increase energy density while compressing the safety margin, while the olivine buffer phase, high blocking current, and structural containment work together to restore the safety margin. Further, this invention also correlates ε with ΔR3 through ΔR3=Σi(ti×ε), allowing the "expansion of high-silicon material" to be quantitatively contained by the "structural gap," thereby effectively solving the deformation and cycling problems of high-silicon cylindrical cells.
[0139] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A cylindrical lithium-ion battery with multiple tabs, characterized in that, The assembly includes a housing and a wound electrode assembly housed within the housing; the wound electrode assembly is formed by winding a positive electrode, a negative electrode, and a separator, and the wound electrode assembly simultaneously satisfies: (a) The contact resistance at the welding connection between the full-pole tab of the positive electrode and the positive current collector is R1, 0.1mΩ<R1≤0.5mΩ; (b) The wound electrode assembly has a central cavity extending axially along the housing, the diameter dcore of which is 8% to 20% of the inner diameter D1 of the housing; (c) In the discharge state, a single-sided radial gap ΔR is reserved between the outer diameter D2 of the wound electrode assembly and the inner diameter D1 of the outer shell, ΔR=(D1-D2) / 2, and ΔR and the radial expansion amount ΔR3 of the electrode assembly when the battery is fully charged satisfy: 1.0≤ΔR / ΔR3≤1.
4.
2. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The positive active material layer includes a composite system of layered lithium nickel cobalt manganese oxide particles and olivine-type lithium manganese iron phosphate particles. The mass percentage of the olivine-type lithium manganese iron phosphate particles in the positive active material layer is x1, where 10% ≤ x1 ≤ 30%. Preferably, the median volume diameter D of the olivine-type lithium manganese iron phosphate particles is... 50(LMFP) The volume median particle size D of the layered lithium nickel cobalt manganese oxide particles is smaller than that of the layered lithium nickel cobalt manganese oxide particles. 50(NCM) And D 50(NCM) / D 50(LMFP) ≥3; Preferably, the constant current charge-discharge differential capacity curve (dQ / dV) of the positive electrode active material layer has at least one characteristic capacity peak in the ranges of 3.4V~3.6V and 3.9V~4.2V.
3. The all-tab cylindrical lithium-ion battery according to claim 2, characterized in that, At least one base coating is provided between the positive electrode current collector and the positive electrode active material layer; The base coating comprises a polymer matrix, a conductive agent, and a ceramic filler; the sheet resistivity R0 of the base coating at 25°C satisfies 0.05 Ω·cm. 2 ≤R0≤2Ω·cm 2 When the temperature rises to 30°C above the trigger temperature Ttrip, the ratio of the sheet resistance Rt to R0 satisfies Rt / R0≥100, where 100°C≤Ttrip≤140°C. Preferably, the thickness tp of the base coating satisfies 1μm≤tp≤3μm.
4. The all-tab cylindrical lithium-ion battery according to claim 2, characterized in that, The negative electrode has an extension δ at both ends of the electrode assembly relative to the positive electrode, where 0.3mm≤δ≤2.0mm.
5. The all-tab cylindrical lithium-ion battery according to claim 2, characterized in that, The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector. The negative active material in the negative active material layer includes silicon-carbon composite particles and a graphite matrix. The silicon-carbon composite particles include nano-silicon particles and a carbon coating layer covering the surface of the nano-silicon particles. The median particle size D of the silicon nanoparticles 50(Si) Satisfying 50nm≤D 50(Si) ≤200nm; The mass fraction W of the carbon coating layer in the silicon-carbon composite particles C Satisfying 8%≤W C ≤20%; Based on elemental silicon, the silicon content W of the negative electrode Si Satisfying 8%≤W Si ≤20%; Preferably, the reversible specific capacity of the negative electrode active material is ≥450mAh / g.
6. The all-tab cylindrical lithium-ion battery according to claim 5, characterized in that, ΔR3 = Σi(ti × ε); where ti is the single-sided thickness of the i-th negative electrode active material layer along the radial direction of the electrode assembly; ε is the full-fill expansion rate of a single negative electrode active material layer, 5% ≤ ε ≤ 20%, and ΔR3 is related to the negative electrode silicon content W. Si There is a positive correlation between them.
7. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The electrolyte in the all-tab cylindrical lithium-ion battery contains film-forming additives, including fluoroethylene carbonate, and the fluoroethylene carbonate accounts for 3wt% to 15wt% of the electrolyte mass.
8. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The separator in the full-tab cylindrical lithium-ion battery is a ceramic-coated composite separator. The pore-closing temperature of the ceramic-coated composite separator is 130℃~160℃, and the thermal shrinkage rate is ≤5% at 150℃.
9. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The all-tab cylindrical lithium-ion battery is a 21650 all-tab cylindrical lithium-ion battery.
10. The all-tab cylindrical lithium-ion battery according to any one of claims 1 to 9, characterized in that, The all-tab cylindrical lithium-ion battery also has at least one of the following characteristics: Feature 1: When the fully charged cylindrical lithium-ion battery is punctured by a steel needle with a diameter of 3-5mm, the maximum surface temperature of the cell is ≤110℃; Feature 2: The full-tab cylindrical lithium-ion battery retains ≥83% of its capacity when charged from 10% SOC to 80% SOC at a constant current of 6C at 25°C, compared to 1C charging. Feature 3: The DC internal resistance (DCIR) of the all-tab cylindrical lithium-ion battery at 25°C and 50% SOC is ≤5mΩ; feature 4: The mass energy density of the all-tab cylindrical lithium-ion battery is ≥250Wh / kg; Feature 5: The full-tab cylindrical lithium-ion battery has a lifespan of ≥1000 cycles under 1C / 1C, 25℃ conditions until 80% SOH.